EVALUATION ON REALISTIC MATHEMATICS EDUCATION INDONESIA IMPLEMENTATION IN FACULTY OF EDUCATION SCIENCES SRIWIJAYA UNIVERSITY PALEMBANG - Pinta Deniyanti Sampoerno (lppm Universitas Negeri Jakarta, 2015)
The objective of this research was to evaluate the effectiveness of PMRI implementation organized by FKIP UNSRI Palembang at two elementary schools in Palembang. It was an evaluation research by Frechting’s Logic Model and by context component as complementary. Triangulation used as credibility test to check the validity of data. Data source triangulation was done to the PMRI central team, PMRI local team, principals, teachers, and students. Meanwhile, data collection techniques triangulation was gotten from questionnaires, interviews, and document observations. Model analysis applied in this research was qualitative. The result of research gave conclusion that the PMRI implementation by FKIP UNSRI has been quite effective. There were several things that have not been appropriate with PMRI standards i.e. the preparation of teaching materials in SDN 98 did not run optimally because the school used regulated thematic teaching materials by provincial government and some teachers did not use evaluation system with PMRI standards.